2014
DOI: 10.7763/ijcea.2014.v5.382
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted Titanium Dioxide Wrinkle Resistant Treatment of Cotton Fabric

Abstract: Abstract-Titanium dioxide (TiO 2 ) has been found feasible for improving the wrinkle resistant of cotton fabric. In this paper, plasma treatment was used as a pretreatment process to enhance the application of TiO 2 in wrinkle resistant treatment of cotton fabric. The relationship between plasma pretreatment process parameters including (i) treatment speed, (ii) oxygen flow rate; and (iii) jet distance were studied through orthogonal array testing strategy (OATS). Based on the OATS, the optimum condition for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Plasma treatment can be used to enhance the resilience of cotton. Kan [158] showed that oxygen APPJ treatment followed by 0.2 % Titanuim dioxide (TiO 2 ) treatment significantly enhanced the wrinkle-resistant property of cotton fabric. This finding was attributed to the etching effect on the fabric surface caused by plasma pretreatment which provides a new pathway for the finishing agent to enter into the fiber, resulting in the formation of more crosslinkages with an increase in the wrinkle recovery angle.…”
Section: Wrinkle-resistant Propertymentioning
confidence: 99%
“…Plasma treatment can be used to enhance the resilience of cotton. Kan [158] showed that oxygen APPJ treatment followed by 0.2 % Titanuim dioxide (TiO 2 ) treatment significantly enhanced the wrinkle-resistant property of cotton fabric. This finding was attributed to the etching effect on the fabric surface caused by plasma pretreatment which provides a new pathway for the finishing agent to enter into the fiber, resulting in the formation of more crosslinkages with an increase in the wrinkle recovery angle.…”
Section: Wrinkle-resistant Propertymentioning
confidence: 99%
“…Among different nanoparticles, titanium dioxide (TiO 2 ) and silver nanoparticles (AgNPs) are two of the nanoparticles which are frequently used in textile applications. TiO 2 nanoparticles are reported to improve UV protection [33], antistatic [35], self-cleaning [3638], antibacterial [39], hydrophilic [40], ultra-hydrophobic [41], wrinkle resistance [42], water adsorption, and dyeability [43,44] properties. In particular, anatase TiO 2 is commonly used for the elimination of microbiological and toxic contaminants in filtration applications and for self-cleaning surface applications [45].…”
Section: Introductionmentioning
confidence: 99%